(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The shortcomings of the accounting systems applied to the cash basis in government institutions in the countries of the world led to the issuance of international accounting standards in the public sector for the purpose of adopting them for countries that wish and have the ability to apply them for the purpose of developing their systems in public sector institutions. Among these standards that were addressed are Standard No. (9) and Standard No. (23), as these two standards aim to determine the necessary bases for reporting useful information to users of the final accounts about the nature, type, amount and timing of revenues. Standard No. (9) and Standard No. (23) will have a significant impact. The most prominent findings of the researcher are the shortcomings of the decentralized government accounting system in the aspect related to revenue recognition and the absence of a local accounting rule related to the revenue element in terms of measurement, recognition and disclosure. The basis for revenue recognition differs between the decentralized government accounting system based on the cash basis with Standard No. (9) and Standard No. (23), which recognizes revenue on an accrual basis. The most prominent recommendations of the researchers are to move from the cash basis used to the accrual basis in accordance with the requirements of international accounting standards in the public sector and legislation. The laws that help to implement this and formulate a new definition of public revenues that is consistent with the approach and conditions of its recognition and adopting the proposed audit program presented by the researcher to assist the external auditor in the auditing process.